Bureaucratic Reform and Public Policy Dynamics: Evaluation Study of One Data Indonesia Program - Umasugi, Mohbir (PT Inovasi Pratama Internasional, 2025)
Bureaucratic reform is one of the strategic agendas in improving the effectiveness and efficiency of governance. One of the main initiatives in this reform is the One Data Indonesia Program, which aims to improve data integration, accuracy, and accessibility to support evidence - based policies. policy). This study aims to evaluate the implementation of One Data Indonesia, identify the challenges faced, and analyze the relationship between public policy theory and the reality of bureaucracy in Indonesia. By using a policy study approach and an evaluation method based on the CIPP model (Context, Input, Process, Product), this study found that this program has succeeded in improving coordination between agencies and transparency in data management. However, a number of obstacles are still faced, such as regulatory inconsistency, bureaucratic resistance, and limited infrastructure and human resource capacity. In addition, there is a gap between the theory of ideal public policy and implementation practices in the field, especially in terms of coordination and openness of data between agencies. The implications of this study emphasize the need for clearer regulatory improvements, increased human resource capacity, strengthened cross-sector coordination, and optimized digital infrastructure to ensure the sustainability of One Data Indonesia. Data-based bureaucratic reform requires not only strong regulations, but also political commitment and implementation strategies that are adaptive to existing challenges.